H2O2-assisted hydrothermal synthesis of TiO2-SiO2 and its enhanced photocatalytic-adsorptive desulfurization performance for model fuel. (15th August 2018) - Li, Xin; Xu, Yilin; Zhang, Chen; Wang, Hong; Song, Yongji; Zhang, Wei; Li, Cuiqing
Highlights: TiO2 -SiO2 -H was synthesized hydrothermally in the presence of H2 O2 . TiO2 -SiO2 -H showed enhanced photocatalytic-adsorptive desulfurization performance. 100% sulfur removal by TiO2 -SiO2 -H required only 1 h of UV irradiation. Abstract: Photocatalytic-adsorptive desulfurization of model fuel by the H2 O2 -assisted synthesized TiO2 -SiO2 (TiO2 -SiO2 -H) was investigated using air as the oxidant under UV irradiation. TiO2 -SiO2 -H was synthesized hydrothermally in the presence of H2 O2 and characterized by scanning electron microscopy (SEM), N2 adsorption, X-ray diffraction (XRD), UV–vis diffuse reflectance spectroscopy (UV–vis DRS) and photoluminescence spectrum (PL). Compared to TiO2 -SiO2 synthesized in the absence of H2 O2, Ti0.25 SiOy -H showed greatly enhanced photocatalytic-adsorptive desulfurization performance due to its increased surface area, greatly increased UV absorption and decreased recombination of photogenerated hole/electron pairs. The Ti/Si molar ratio was optimized to 0.3 with the sulfur removal of 100% after reaction for 1 h at the fuel-to-Ti0.3 SiOy -H weight ratio of 20, and the sulfur content could still be reduced to be <1 ppmw when the fuel-to-Ti0.3 SiOy -H weight ratio was increased to 80. Moreover, TiO2 -SiO2 -H based photocatalytic-adsorptive process bears high selectivity for removing organosulfur in the toluene-containing fuel. The sulfur removal for model fuel containing 25 wt% toluene could reach 98.4% after reaction for 5 h. The photocatalytic-adsorptive selectivity of Ti0.3 SiOy -H for organosulfur compounds in model diesel fuels followed the order of dibenzothiophene > 4, 6-dimethyldibenzothiophene > benzothiophene. The desulfurization performance of TiO2 -SiO2 -H was basically stable after four consecutive desulfurization-regeneration cycles.